KINGYO NO OTSUKAI: CONTRIBUTION OF THE VALUE OF JAPANESE WORK ETHICS FOR CHILDREN - Eduardus Agusli; Tienn Immerry; Femmy Dahlan (Universitas Andalas, 2021)
Japanese customs in practicing work ethics and upholding the principles of life are outstanding. These outstanding values were due in part to the instilled at an early age. A simple children’s story entitled Kingyo no Otsukai can be used as educational material for children because it portrays the value of Japanese work ethics. The research method applied was a descriptive qualitative method. Art and culture underlie the appreciation of literary work. Literary work is useless if it cannot interpret the goals carried out by the author. Kingyo no Otsukai contributes to children through the values of Japanese work ethics,namely bushido, makoto and ganbatte, also keishan. The connection among these three work ethics is the principle of bushido with optimism in doing everything, plus the spirit of ganbatte (never give up), supported by makoto (honesty and sincerity) to improve one’s abilities with creativity, productivity and innovation (Keishan). The embodiments of the Koinobori celebration in Japanese society are the three goldfish (the Red, the White, and the Striped) in the story. Japanese families with sons will celebrate every May 5th wishing the child success and progress. It is the task of parents or teachers to transfer the value of the work ethics obtained from children’s stories to children.